2000
DOI: 10.1097/00000421-200006000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin, 5-Fluorouracil, and Folinic Acid (Folfox) in Patients With Metastatic Renal Cell Carcinoma

Abstract: We report the results of a chemotherapy regimen combining oxaliplatin, 5-fluorouracil, and folinic acid in patients with metastatic renal cell carcinoma. The objective of this pilot study was to define the potential efficacy of this second-line combination in patients previously treated with interleukin-2 alone or in combination with interferon alpha. Fourteen patients with metastatic renal cell carcinoma in failure after immunotherapy were included in this trial. During treatment, patients received six chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Phase II trials conducted with new agents such as taxanes or gemcitabine were ineffective as well [6, 7]. The negative results of our study confirm those of a recent pilot study in which 14 patients previously treated by cytokines failed to respond to the FOLFOX-4 regimen [8]. These two trials indicate that further studies with oxaliplatin are not profitable in this disease.…”
Section: Discussionsupporting
confidence: 66%
“…Phase II trials conducted with new agents such as taxanes or gemcitabine were ineffective as well [6, 7]. The negative results of our study confirm those of a recent pilot study in which 14 patients previously treated by cytokines failed to respond to the FOLFOX-4 regimen [8]. These two trials indicate that further studies with oxaliplatin are not profitable in this disease.…”
Section: Discussionsupporting
confidence: 66%
“…Oxaliplatin is a platinum-based chemotherapy and is typically used in combination therapies for the treatment of colorectal cancer. Early clinical trials showed that oxaliplatin is ineffective against advanced RCC (3,4). One of the major mechanisms of platinum resistance in this cancer type is inadequate amounts of platinum reaching the target DNA (5).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, no objective responses were observed in either a small pilot study of the FOLFOX-4 (5-FU, leucovorin, and L-OHP) regimen 26 or a larger (n ϭ 59) Phase II study of the same regimen. 27 In conclusion, our results suggest a certain level of activity, with an acceptable toxicity profile, for the FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%